2002
DOI: 10.1038/sj.bjp.0704625
|View full text |Cite
|
Sign up to set email alerts
|

Gastric antisecretory role and immunohistochemical localization of cannabinoid receptors in the rat stomach

Abstract: 1 The role of cannabinoid (CB) receptors in the regulation of gastric acid secretion was investigated in the rat by means of functional experiments and by immunohistochemistry. 2 In anaesthetized rats with lumen-perfused stomach, the non selective CB-receptor agonist WIN 55,212-2 (0.30 ± 4.00 mmol kg 71 , i.v.) and the selective CB 1 -receptor agonist HU-210 (0.03 ± 1.50 mmol kg 71 , i.v.), dose-dependently decreased the acid secretion induced by both pentagastrin (30 nmol kg 71 h 71 ) and 2-deoxy-D-glucose (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 32 publications
6
68
0
2
Order By: Relevance
“…For example they inhibit GI transit and motility in rats (Landi et al, 2002), decrease the intragastric pressure and the pyloric contractility by activating CB 1 receptors (Krowicki et al, 1999), tonically inhibit colonic propulsion (Pinto et al, 2002) and decrease GI transit in mice (Izzo et al, 2000). CB 1 receptor agonists decreased the gastric acid secretion induced by pentagastrin given intravenously (Adami et al, 2002), but i.c.v. injection of the synthetic non-selective agonist WIN 55,212-2 was ineffective in preventing the pentagastrin stimulated gastric acid secretion (Adami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example they inhibit GI transit and motility in rats (Landi et al, 2002), decrease the intragastric pressure and the pyloric contractility by activating CB 1 receptors (Krowicki et al, 1999), tonically inhibit colonic propulsion (Pinto et al, 2002) and decrease GI transit in mice (Izzo et al, 2000). CB 1 receptor agonists decreased the gastric acid secretion induced by pentagastrin given intravenously (Adami et al, 2002), but i.c.v. injection of the synthetic non-selective agonist WIN 55,212-2 was ineffective in preventing the pentagastrin stimulated gastric acid secretion (Adami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids were shown to inhibit gastrointestinal motility (Izzo et al, 1999;Krowicki et al, 1999), gastric acid secretion (Adami et al, 2002) and development of gastric mucosal lesions both in acid-dependent (Germano et al, 2001;Rutkowska and Fereniec-Goltbiewska, 2006) and acid-independent ulcer models (Shujaa et al, 2009). Accordingly, CB 1 receptors were identified in neurons of the enteric nervous system and in sensory terminals of vagal and spinal neurons, moreover, CB 1 receptors are also identified in the dorsal vagal complex: in the nucleus of the solitary tract (NTS) (Partosoedarso et al, 2003), in the dorsal motor nucleus of vagus (DMNV) (Mackie, 2005) and prominently, in the area postrema (Mackie, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CB 1 -receptor activation by the potent agonist HU-210 reduced neurogenic ion transport elicited by the proinflammatory peptide kallidin (15). Gastric secretion evoked by pentagastrin and 2-deoxy-D-glucose was also inhibited by CB 1 receptor agonists, and the receptor was identified on myenteric cholinergic neurons and/or vagal pathways in the myenteric plexus (1). These studies have recently been extended to show that endogenous cannabinoids play a role in the regulation of fluid secretion.…”
mentioning
confidence: 90%
“…However, recent reports (1,15,40) suggest that cannabinoid (CB) receptors of the CB 1 subtype may also suppress neurally evoked secretion. Tyler et al (40) showed that CB 1 receptors could reduce secretion evoked by electrical field stimulation (EFS) but not that evoked by acetylcholine in the rat ileum.…”
mentioning
confidence: 99%
“…La distribución de los receptores CB1 similar a la de la grelina o al péptido similar al glucagon (GLP1, glucagon like peptide 1) y en estructuras neurales modulando transmisión colinérgica y no colinérgica (Adami, Frati, Bertini, Kulkarni-Narla, Brown, de Caro et al 2002;Storr, Gaffal, Saur, Schusdziarra y Allescher, 2002), sugieren que forman parte de las conexiones entre tubo digestivo y cerebro regulando la conducta alimentaria.…”
Section: El Receptor Cb1 Y La Enzima Amidohidrolasa De áCidos Grasos unclassified